Pengaruh Promosi dan Kualitas Pelayanan terhadap Kepuasan Pelanggan pada Nuri Mart di Bekasi - Mutmainnah Mutmainnah; Ahmad Dimyati (Journal on Education, 2023)
This study aims to determine how much influence promotions have on customer satisfaction at Nuri Mart, to find out how much influence service quality has on customer satisfaction at Nuri Mart, to find out how much influence promotion and service quality together have on customer satisfaction at Nuri Mart. The research method used is quantitative. The population in this study are Nuri Mart customers. By using a sample of 100 respondents. Data collection techniques by means of observation, and distributing questionnaires (questionnaires) and data analysis techniques are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, simple and multiple linear regression analysis, coefficient of determination analysis and hypothesis testing (test t) and (F test). The results of this study indicate that there is an influence between promotions on customer satisfaction at Nuri Mart with the results of the partial test (t test) between promotions (X1) and customer satisfaction (Y) showing the value of t count > t table (3.616 > 1.660) and sig < 0.005 (0.000 < 0.005). And there is an effect of service quality on customer satisfaction at Nuri Mart with the results of a partial test (t test) between service quality (X2) on customer satisfaction (Y) showing the value of t count > t table (3.121 > 1.660) and sig < 0.005 (0.002 < 0.005). Based on the results of the simultaneous test (f test) obtained the calculated F value > F table or (18.297 > 3.939) this is also reinforced by a significance probability value of 0.000 < 0.005, which means that there is a significant influence between promotion and service quality on Nuri Mart's customer satisfaction.